Improve the public key schemes by using keys based on different polynomials - AL-Swidi, Ameer A. J.; Al-Saadi, Lamis Hamood; Al-Saadi, Enas Hamood (International Journal of Psychosocial Rehabilitation, 2020)
Many researchers have studied the development and updating of RSA method and methods with the key, where these methods depend on the powers and confidentiality of the keys. In our research, we worked on these keys, which are numbers and for confidentiality we treated them as polynomial where the recipient of the cipher worked to solve them and return them as numbers. These polynomials were built with specific theories based on partial differential equations where they gave positive results achieved through examples.